Simulation of improper food hygiene practices: A quantitative assessment of Vibrio parahaemolyticus distribution - Malcolm, Tan Turk Hsern; Chang, Wei San; Loo, Yuet Ying; Cheah, Yoke Kqueen; Wan Mohamed Radzi, Che Wan Jasimah; Kantilal, Haresh Kumar; Nishibuchi, Mitsuaki; Son, Radu (Elsevier, 2018)
Kitchen mishandling practices contribute to a large number of foodborne illnesses. In this study, the transfer and cross-contamination potential of Vibrio parahaemolyticus from bloody clams to ready-to-eat food (lettuce) was assessed. Three scenarios were investigated: 1) direct cross-contamination, the transfer of V. parahaemolyticus from bloody clams to non-food contact surfaces (hands and kitchen utensils) to lettuce (via slicing), was evaluated; 2) perfunctory decontamination, the efficacy of two superficial cleaning treatments: a) rinsing in a pail of water, and b) wiping with a kitchen towel, were determined; and 3) secondary cross-contamination, the microbial transfer from cleaning residuals (wash water or stained kitchen towel) to lettuce was assessed. The mean of percent transfer rates through direct contact was 3.6%, and an average of 3.5% of total V. parahaemolyticus was recovered from sliced lettuce. The attempted treatments reduced the transferred population by 99.0% (rinsing) and 94.5% (wiping), and the relative amount of V. parahaemolyticus on sliced lettuce was reduced to 0.008%. V. parahaemolyticus exposure via secondary cross-contamination was marginal. The relative amount of V. parahaemolyticus recovered from washed lettuce was 0.07%, and the transfers from stained kitchen towel to lettuce were insubstantial. Our study highlights that V. parahaemolyticus was readily spread in the kitchen, potentially through sharing of non-food contact surfaces. Results from this study can be used to better understand and potentially raising the awareness of proper handling practices to avert the spread of foodborne pathogens.